1993
DOI: 10.2307/3869710
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Age-Related Processes That Influence the Longevity and Senescence of Photosynthetic Tissues in Arabidopsis

Abstract: Factors that influence the longevity and senescence of photosynthetic tissues of Arabidopsis were investigated. To determine the influence of reproductive development on the timing of somatic tissue senescence, the longevity of rosette leaves of the Landsberg erecta strain and of isogenic mutant lines in which flowering is delayed (co-2) or sterile flowers are produced (ms1-1) were compared. No difference in the timing of senescence of individual leaves was observed between these lines, indicating that somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 0 publications
3
76
0
2
Order By: Relevance
“…While regulation of transcription has been implicated in some of these processes, post-transcriptional control is often a primary regulatory determinant (21,23,26,29,31,32). This current study indicates that post-transcriptional control was utilized as a primary mechanism when RbcS gene expression was adapted for the specialized cell-type specific expression that provides the foundation for the C 4 pathway in F. bidentis leaves.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While regulation of transcription has been implicated in some of these processes, post-transcriptional control is often a primary regulatory determinant (21,23,26,29,31,32). This current study indicates that post-transcriptional control was utilized as a primary mechanism when RbcS gene expression was adapted for the specialized cell-type specific expression that provides the foundation for the C 4 pathway in F. bidentis leaves.…”
Section: Discussionmentioning
confidence: 71%
“…Rubisco genes are known to be highly regulated; in many plants their expression is modulated by light (18,23,24), development (20,25,26), cell type (6, 9, 16), photosynthetic metabolism (17,19,(27)(28)(29), and even pathogen infection (30). While regulation of transcription has been implicated in some of these processes, post-transcriptional control is often a primary regulatory determinant (21,23,26,29,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the expression of several senescence-associated genes has been suggested to be directly coupled to the decline of photosynthetic activity, which reduces the cellular sugar levels in leaves (57). Since the transcripts from the E1␤ and E2 subunits accumulated in the senescing leaves, BCKDH may be involved in the utilization of the carbon skeletons of branchedchain amino acids as an energy source during leaf senescence as well as sugar starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the elucidation of the genetic control of senescence in leaves has proved difficult (R. Amasino, personal communication), several groups have resorted to molecular approaches to identifying genes likely to be involved in senescence control. Several genes (termed SAG for senescence-associated genes) which show sequence similarity to cysteine proteases are induced early during senescence (32,33). Because (43) showed that enhancing H202 production during the HR led to dramatic increases in the amount of cell death observed in a soybean cell culture system.…”
Section: Senescencementioning
confidence: 99%